DETECTION OF CLAMPING FORCES ON MOUNTING A CONSTRUCTION VIA NEURAL NETWORK FOR THE FINITE-ELEMENT MODEL OF COMPRESSOR-CONDENSING UNIT - S. V. Krasnovskaya (Informatika, 2017)
The article provides a brief review of a condensing unit and problems of mathematic simulation. It examines the influence of pretension on the strain-stress state of a construction by means of finiteelement modeling. The arrangement of a set of input-output data for neural network is also considered. The article investigates a possibility to predict mounting precision via neural networks; by analogy with the above calculations it examines the option to detect clamping forces on mounting compressorcondensing unit.